Alone in the dark - Boll, Uwe; Slater, Christian; Reid, Tara, 1975-; Dorff, Stephen, 1973- (Santa Monica, Calif. : Lions Gate Home Entertainment, 2005)
Edward Carnby is a private investigator specializing in the paranormal. Together, he, his ex-girlfriend, and his bitter rival investigate a dangerous case involving a mystery in his past.
Based on the video game by Atari.
Originally released as a motion picture in 2005.
Features: commentary with director Uwe Boll, making-of featurette, trivia track, music videos, storyboard to film comparisons.
Christian Slater, Tara Reid, Stephen Dorff, Frank C. Turner, Mathew Walker.
MPAA rating: R.
DVD, Dolby digital 5.1 surround.
Keywords: Private investigators -- Drama; Supernatural -- Drama; Video recordings for hard of hearing people; Feature films; Horror films